Trend 1990 - 2011. Energy Information Administration. International Energy Statistics: Natural Gas Exports | Country: Greenland | Indicator: Total Dry Natural Gas Exports (Billion Cubic Feet), 1990-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 004-014-015. - Energy Information Administration (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Energy Information Administration (2015). International Energy Statistics: Natural Gas Exports | Country: Greenland | Indicator: Total Dry Natural Gas Exports (Billion Cubic Feet), 1990-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 004-014-015. Dataset: Provides statistics on natural gas exports by country, as available. Natural gas imports include liquefied natural gas (LNG). Dry natural gas is the gas that remains after: the liquefiable hydrocarbon portion has been removed from the gas stream (ie, gas after lease, field, and/or plant separation); and any volumes of non-hydrocarbon gases have been removed where they occur in sufficient quantity to render the gas unmarketable. Dry natural gas is also known as consumer-grade natural gas. The dataset provides data for 220 countries, as available, on energy-related metrics, including total and crude oil production, oil consumption, natural gas production and consumption, coal production and consumption, electricity generation and consumption, primary energy, energy intensity, CO2 emissions and imports and exports for all fuels. Data are sourced from Energy Information Administration research, as well as from national and international agencies, listed at http://www.eia.gov/cfapps/ipdbproject/docs/sources.cfm. Category: Energy Resources and Industries, International Relations and Trade Source: Energy Information Administration The Energy Information Administration (EIA), created by Congress in 1977, is an independent statistical and analytical agency within the United States Department of Energy. Its mission is to provide policy-independent data, forecasts, and analyses to promote sound policy making, efficient markets, and public understanding regarding energy and its interaction with the economy and the environment. http://www.eia.doe.gov/ Subject: Natural Gas, Exports, International Trade